2015
DOI: 10.3899/jrheum.141629
|View full text |Cite
|
Sign up to set email alerts
|

Does Rheumatoid Cachexia Predispose Patients with Rheumatoid Arthritis to Osteoporosis and Vertebral Fractures?

Abstract: Our study showed that half of the patients with RA may have RC, a condition that was significantly associated with disease activity and low hip BMD, but not with VF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
31
1
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 46 publications
1
31
1
1
Order By: Relevance
“…There has been recent interest in the impact of muscle loss on bone loss among patients with RA (12, 13). We are aware of only one previous study characterizing associations between muscle area and cortical dimensions in women with RA using pQCT (14).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There has been recent interest in the impact of muscle loss on bone loss among patients with RA (12, 13). We are aware of only one previous study characterizing associations between muscle area and cortical dimensions in women with RA using pQCT (14).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the direct effects of inflammation on bone remodeling, muscle loss and adverse fat distribution may also contribute to adverse bone outcomes (510). However, few studies have evaluated associations between body composition and bone outcomes in RA (11–13), and only one previous study compared these associations to those observed in controls (14). …”
Section: Introductionmentioning
confidence: 99%
“…Mean while, the tools available for evaluating and staging RC have become more precise and can more adequately define the effects of inflammatory conditions on lean mass, fat mass and energy expenditure [12]. [9]. It is therefore evident that the prevalence of malnutrition, according to the criterion of decreased lean mass, is frequently underestimated.…”
Section: Introductionmentioning
confidence: 99%
“…In recent decades, the concept of rheumatoid cachexia has received more consideration [5] based on the understanding of how nutritional alterations affect patient quality of life, evolution and the prognosis of rheumatologic conditions such us increased risk of cardiovascular disease and osteoporosis [8,9]. Advances have also been made in our comprehension of the pathophysiological mechanisms that mediate the nutritional impact of inflammatory diseases (acute and chronic) [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the factors described above, there are a number of traditional risk factors for fracture that are not specific to RA because onset of RA tends occur later in life of women, with a peak around the age of menopause. These include being female, increasing age, a postmenopausal state, being underweight, cigarette smoking, high alcohol intake and increased falls risk [1,4].…”
mentioning
confidence: 99%